Brunner's gland hyperplasia: an unusual duodenal submucosal lesion seen in four patients. Issue 11 (30th November 2018) - Bojanapu, Srinivas; Mangla, Vivek; Mehrotra, Siddharth; Lalwani, Shailendra; Mehta, Naimish; Nundy, Samiran
Abstract: Brunner's gland hyperplasia is an extremely rare benign hamartomatous lesion seen in proximal duodenum. Difficulty in diagnosing the condition pre-operatively puts the surgeon in dilemma for deciding appropriate management. We retrieved details from prospectively maintained retrospective data from January 2014 to April 2018. Four patients were identified of which three were males and one was female. Symptoms ranged from 4 days to 4 years, with abdominal pain, vomiting and malena being predominant. No patients were identified with diagnosis pre-operatively. Diagnosis was made on histopathological examination of the resected specimen and none of them were having malignant features. At a median follow up of 11 months, no patient had recurrence and were symptom free. Brunner's gland hyperplasia is a rare elusive duodenal pathology, symptomatically mimicking alarming duodenal lesions and mostly diagnosed on histopathology of specimen. Patients may harbour the lesion for long periods with little symptoms and upon treatment have good outcomes.